Clinical value of high-sensitivity cardiac troponin assays after acute ischemic stroke - Yi-rui CAO; Bo WU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2016)
In view of a variety of cardiovascular events complicated by acute ischemic stroke, the importance of monitoring myocardial ischemic symptoms and signs, electrocardiogram, echocardiogram and myocardial injury markers has been gradually recognized by clinicians. Cardiac troponin (cTn) by conventional assay has been a unique marker of myocardial injury for its extremely high specificity. However, with the utilization of high-sensitivity cardiac troponin (hs-cTn), cTn is no longer exclusive of a disease, but was given more significance in the diagnosis and application value. Therefore, we described the clinical significance of alterations of serum hs-cTn concentration after ischemic stroke.   DOI: 10.3969/j.issn.1672-6731.2016.11.015